1992
DOI: 10.1093/ajcn/55.5.971
|View full text |Cite
|
Sign up to set email alerts
|

Glycine, leucine, and phenylalanine flux in low-birth-weight infants during parenteral and enteral feeding

Abstract: Kinetics of three amino acids with different sites and characteristics of metabolic regulation were studied in low-birth-weight infants during enteral and parenteral feeding regimens typical of clinical practice. Primed constant infusions of [15N]glycine, L-[1-13C]leucine, and L-[1-13C]phenylalanine were administered simultaneously by the same route as the feeding, with isotope enrichment measured in urine over 12 h. The effect of feeding regimen was specific to each amino acid (mean +/- SD): glycine flux was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Isotopic enrichment of threonine was similar in plasma and urine (plasma-to-urine enrichment ratio of 0.966 ± 0.010; x -± SEM, n = 14), thus validating the measurement of [ 13 C]threonine enrichment in urine as opposed to plasma (23,30). The mean (± SEM) CV of urinary threonine enrichment above baseline at plateau was 5.2 ± 1.6% (n = 14).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Isotopic enrichment of threonine was similar in plasma and urine (plasma-to-urine enrichment ratio of 0.966 ± 0.010; x -± SEM, n = 14), thus validating the measurement of [ 13 C]threonine enrichment in urine as opposed to plasma (23,30). The mean (± SEM) CV of urinary threonine enrichment above baseline at plateau was 5.2 ± 1.6% (n = 14).…”
Section: Resultsmentioning
confidence: 58%
“…Threonine flux was measured from the dilution of the infused tracer in the metabolic pool at isotopic steady state, as described previously (23,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data from research in seven normal growing newborns aged 20 d have been reported with endogenous production rates of phenylalanine equal to a mean of 87 kmol/kg/h (23). In 12 low-birth-weight infants, the phenylalanine flux, calculated from infusions of ~-[ l -~~~]~h e n~l a l a n i n e , during enteral and parenteral feeding was 106 and 56 kmol/kg/h, respectively (24).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to values for term infants, previous work has demonstrated similar hydroxylation rates of 22 kmol/kg/h for conversion of phenylalanine to tyrosine. This constituted 25% of the total phenylalanine flux (24).…”
Section: Discussionmentioning
confidence: 99%